Single-Cell Landscape of the Cochlea Revealed Cell-Type-Specific Diversification in Hipposideros armiger Based on PacBio Long-Read Sequencing - Mingyue Bao; Xue Wang; Xintong Li; Ruyi Sun; Zhiqiang Wang; Tinglei Jiang; Hui Wang; Jiang Feng (Biomolecules)
Echolocation represents one of the most rapid adaptive sensorimotor modulation behaviors observed in mammals, establishing bats as one of the most evolutionarily successful mammals. Bats rely on high-frequency hearing for survival, but our understanding of its cellular molecular basis is scattered and segmented. Herein, we constructed the first single-cell transcriptomic landscape of the cochlea in Hipposideros armiger, a CF-FM bat, using a PacBio-optimized genome and compared it with the results obtained from unoptimized original genomes. Sixteen distinct cell types were distributed across five spatial regions of the cochlea. Notably, through hematoxylin and eosin staining and fluorescence in situ hybridization, we identified new types of spiral ganglion neuron (SGN) cells in the cochlea of H. armiger. These SGN cells are likely critical for auditory perception and may have driven the adaptive evolution of high-frequency hearing in this species. Furthermore, we uncovered the differentiation relationships of among specific cell types, such as the transition from supporting cells to hair cells. Using the cochlear cell atlas as a reference, cell types susceptible to deafness-associated genes (in the human) were also identified. In summary, this study provides novel insights into the cellular and molecular mechanisms underlying the adaptive high-frequency hearing in bats and highlights potential candidate cell types and genes for therapeutic interventions in hearing loss.